Current Knowledge of Progestin-Only Pills (2021)
Since the 1960s, contraceptive pills have been at the service of humanity. They are one of the innovations that have contributed the most to the changing role of women in society and to women achieving the role they play today. Combined oral contraceptives (COCs) opened up opportunities to increase knowledge about the effects of estrogens and progestins in the female organism. The overall results of this evolution were progestin-only contraceptives in general and estrogen-free oral contraceptives as progestin-only pills (POPs) in particular. To identify the position currently held by POPs, a bibliographic review was carried out in the following databases: PubMed, ScienceDirect, EBSCOhost, OvidSP, Embase, and SciELO in Spanish. POPs have evolved notably from restricted use only during breastfeeding to a broader context. The absence of estrogen in the pill currently offers more advantages than disadvantages. The recent introduction of POP containing 4.0 mg of drospirenone, administered in a 24/4-day regimen, offers better cycle control than previous POPs, as it allows much more predictable bleedings and the same contraceptive efficacy as COCs. Hormonal contraception use continues to grow. The options to regulate reproduction are numerous, and users have a greater number of options to choose the one that suits their needs and comforts. Health professionals must provide high-quality contraceptive counseling, offering all available tools, including POPs.